THE ROLE OF DIGITAL COMPETENCE OF HUMAN RESOURCES OF MSMES IN MEDAN CITY IN IMPROVING ORGANIZATIONAL PERFORMANCE IN THE INDUSTRY 4.0 ERA - Rismaja Putra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to examine the role of human resource (HR) digital competency in improving the organizational performance of micro, small, and medium enterprises (MSMEs) in Medan City in the era of Industry 4.0. A quantitative approach with a survey design was employed, involving 85 MSME owners selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results confirm that HR digital competency positively and significantly affects MSME organizational performance (β = 0.621; t = 7.843; p < 0.001; R² = 0.514). All five digital competency dimensions, digital literacy, digital security, digital communication, digital problem-solving, and digital content creation, demonstrated significant partial effects, with digital literacy as the most dominant dimension (β = 0.538). These findings underscore the strategic urgency of HR digital competency development for improving MSME performance in Medan City and provide an evidence base for policymakers in designing differentiated, evidence-based digital training programs.